Calcification Detection in Breast Cancer - Kaur, Mandeep (International Journal of Psychosocial Rehabilitation, 2020)
One quarter of the all categories of cancer detected among females is breast cancer. This is the main reason for 18% of deaths from cancer worldwide. Up to now, Breast cancer was the major reason of the death among females however, since 1985 it has been ranked second after lung cancer. It is not possible to prevent this cancer due to the lack of adequate knowledge regarding its cause. Nevertheless, modern treatment technologies are extremely efficient against breast cancer. Using these technologies, it is possible to detect this cancer in its early stage. It is very difficult to feel these calcium bits due to their tiny size. However, these bits can appear on a mammogram in form of tiny, bright white spots. These bits can be a reason of worry. Therefore, more tests are required. As an example, tense clusters or lines of minute calcifications may be the symptom of breast cancer. Calcifications are frequent. Around half of all mammograms in women ages 50 and older have calcifications. There may be many reasons behind calcifications. In this research work, the hybrid classification method will be proposed for the calcification of breast cancer. The proposed approach will be implemented in MATLAB and results in terms of certain parameters.